PSYCHOLOGICAL WELL-BEING: THE INVISIBLE BRIDGE TO WORK ENGAGEMENT - Sugiyanto; Lubis, Rahmi; Fadilah, Risydah (Pena Cendekia Insani, 2025)
This study aims to examine the mediating role of psychological well-being (PWB) in the relationship between perceived organizational support (POS) and work engagement (WE) among public sector employees. A total of 406 respondents were drawn from BPJS Ketenagakerjaan staff across Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that POS significantly and positively affects both PWB and WE, while PWB has a dominant effect on WE. Mediation analysis confirms that PWB significantly mediates the effect of POS on WE, indicating that organizational support influences engagement more strongly when it enhances employees’ psychological well-being. Multi-group analysis further shows differing mechanisms between structural and non-structural positions: for structural employees, PWB serves as the primary pathway, whereas for non-structural employees, POS has a more direct effect on WE. These findings emphasize the importance of organizational support that fosters psychological well-being to strengthen work engagement, while also contributing to theoretical development of engagement within Indonesia’s public sector context.